Are long-run output growth rates falling? - Mengheng Li; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2018)
This paper studies the evolution of long-run output and labour productivity growth rates in the G-7 countries during the post-war period. We estimate the growth rates consistent with a constant unemployment rate using time-varying parameter models that incorporate both stochastic volatility and a Heckman-type two-step estimation procedure that deals with the possible endogeneity problem in the econometric models. The results show a significant decline in long-run growth rates that is not associated with the detrimental effects of the Great Recession, and that the rate of growth of labour productivity appears to be behind the slowdown in long-run GDP growth.
Keywords: O41; O47; C15; C32; 330; long-run output growth rates; unobserved components; Kalman filter; timevarying parameter models; stochastic volatility; Heckman two-step bias correction